Growth hormone deficiency after treatment of acute leukaemia in children. Issue 7 (July 1976) - Shalet, S M; Beardwell, C G; Jones, P H; Pearson, D
Abstract : Growth hormone (GH) secretion was studied in 15 children at various times after treatment for acute lymphatic leukaemia. Impaired GH responses both to hypoglycaemia and to Bovril were found in 4 children. 13 of the children had been given prophylactic cranial irradiation of either 2500 rads in 10 fractions or 2400 rads in 20 fractions. The reduction in GH responses in those given the former dose was highly significant compared with the reduction in those given the latter dose. However, other differences between the two groups included the length of time since cranial irradiation and the chemotherapy used. The main cause of the GH deficiency is not yet clear, but we conclude that it may occur in children treated successfully for acute lymphatic leukaemia.